ANALISIS MIKROSATELIT PADA SAMPEL FESES GAJAH SUMATERA (Elephas maximus sumatranus) DI TAMAN NASIONAL TESSO NILO, RIAU - Beno Fariza Syahri; Haris Gunawan; Herawati Sudoyo (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Sumatran elephant (Elephas maximus sumatranus) is an endemic land mammal on Sumatra Island which now is on critically endangered. The population of Sumatran elephant in Riau Province spread in 9 pouches of population, one of them is population in Tesso Nilo National Park (TNNP). Habitat fragmentation and land conversion in protected areas caused condition of Sumatran elephant’s population had deteriorated. Therefore, we need a precise conservation effort to save the population of Sumatran elephant in TNNP. These efforts require appropriate information on the number of individuals and population genetic. The aims of this study were to determine the number of individuals, variation and frequency of allele, and the level of heterozygosity of Sumatran elephant population in TNNP based on genetic information. Molecular analysis using microsatellite marker was performed on 108 non-invasive samples which were collected using CMR method. The result revealed that there were 73 individuals of Sumatran elephant in TNNP. The average number of allele variation from 13 microsatelite loci which were analized was 2.85 allele/locus with average observed heterozygosity (0.507) is higher than expected heterozygosity (0.490). Those indicates that allele frequencies found to be above of the Hardy-Weinberg equilibrium. This studyproved that there is no genetic pressure of Sumatran elephant population in TNNP.